Metal-free sulfonyl radical-initiated cascade cyclization to access sulfonated indolo[1, 2-a]quinolines. Issue 84 (3rd October 2019) - Sun, Kai; Chen, Xiao-Lan; Zhang, Yin-Li; Li, Kai; Huang, Xian-Qiang; Peng, Yu-Yu; Qu, Ling-Bo; Yu, Bing
Abstract : A metal-free cascade reaction was developed for the synthesis of indolo[1, 2- a ]quinoline derivatives from arylsulfonyl hydrazides and 1-(2-(arylethynyl)phenyl)indoles in the presence of TBAI/TBHP. Abstract : A metal-free cascade reaction was developed for the synthesis of indolo[1, 2- a ]quinoline derivatives from arylsulfonyl hydrazides and 1-(2-(arylethynyl)phenyl)indoles in the presence of TBAI/TBHP. Impressively, these products exhibit excellent fluorescence properties, which is promising for cell imaging.